Interseismic Megathrust Coupling at the Osa Peninsula, Costa Rica - Perry, Mason; Muller, Cyril; Protti, Marino; Feng, Lujia; Hill, Emma M. (Journal of geophysical research. Solid earth, 2025)
At the Osa Peninsula in southern Costa Rica, magnitude >7 earthquakes have been generated along the Middle American trench in 1904, 1941, and 1983 following a ∼40‐year recurrence interval, suggesting a rupture may be impending. However, regional interseismic coupling remains poorly constrained, largely due to sparse observations that are likely contaminated by aliasing effects of repeating shallow slow slip events (SSEs) that occur roughly every 4 years, but were only discovered recently. These SSEs, while likely reducing megathrust coupling near the trench, may load or trigger the next rupture of the 1983 asperity. Using new continuous Global Navigation Satellite System (GNSS) data from an updated and densified regional network, we derive inter‐SSE rates of deformation and invert for slip deficit and megathrust coupling along the Middle American Trench, implementing block modeling to correct for the motion of the Panama microplate. We invert for slow slip and remove a time‐averaged estimate of cumulative slow slip from our models. Our results indicate that the region of highest inter‐SSE coupling (>0.8) corresponds with the spatial extent of SSE slip. We also find that SSEs are sufficient to release nearly all the elastic strain accumulated over their 4‐year recurrence interval in localized regions. Accounting for this, in the region immediately downdip of the slow slip patch—the same region thought to have ruptured in the 1983 Mw 7.4 event—we estimate an interseismic coupling ratio of ∼0.5–0.7 corresponding to ∼1.75–2 m of accumulated slip deficit since 1983, sufficient to generate a similar magnitude rupture in the future. Plain Language Summary Megathrust coupling at the Osa Peninsula of Costa Rica has historically been poorly constrained due to sparse observations, but accurate coupling estimates are vital for understanding and forecasting seismic hazard in the region. The megathrust offshore southern Costa Rica has been host to a number of historical earthquakes, generating magnitude >7 events in 1904, 1941, and most recently 1983, following a ∼40‐year recurrence interval. This pattern of earthquakes suggests a rupture may be impending, emphasizing the urgent importance of understanding the location and behavior of frictionally locked asperities on the megathrust. In this paper we present new estimates of coupling based on data from an updated and densified regional geodetic observation network. We also account for the influence of slow slip events (effectively slow earthquake ruptures) on estimates of megathrust coupling. Overall, we find that enough strain has accumulated on the megathrust at the Osa Peninsula to generate an earthquake as large as the 1983 Mw 7.4 event. Key Points The Osa Peninsula has been subject to large (magnitude > 7) earthquakes every ∼40 years, most recently in the 1983 magnitude 7.4 event A new geodetic coupling model indicates the region of the 1983 rupture has accumulated enough strain to host a similar magnitude event Slow slip events reduce the overall coupling in localized patches and may influence spatial patterns of a future rupture